Efficient oxidation of oleanolic acid derivatives using magnesium bis(monoperoxyphthalate) hexahydrate (MMPP): A convenient 2-step procedure towards 12-oxo-28-carboxylic acid derivatives - Salvador, Jorge A. R.; Moreira, Vânia M.; Pinto, Rui M. A.; Leal, Ana S.; Paixão, José A. (Beilstein Journal of Organic Chemistry, 2012)
A new, straightforward and high yielding procedure to convert oleanolic acid derivatives into the corresponding δ-hydroxy-γ-lactones, by using the convenient oxidizing agent magnesium bis(monoperoxyphthalate) hexahydrate (MMPP) in refluxing acetonitrile, is reported. In addition, a two-step procedure for the preparation of oleanolic 12-oxo-28-carboxylic acid derivatives directly from Δ12-oleananes, without the need for an intermediary work-up, and keeping the same reaction solvent in both steps, is described as applied to the synthesis of 3,12-dioxoolean-28-oic acid.
Keywords: bismuth(III) triflate; δ-hydroxy-γ-lactones; MMPP; oleanolic acid; triterpenoid